Assessing decision making practice (in case of Queens College Adminstiration in Kality branch) - Alehegn, Derese Simegnew (Technium Business and Management, 2022)
The study was to assess the decision making practice in Queens College Administration. Participatory decision making offered valuable opportunities to focus on work activity, goals to identify, correct existing problems and to encourage better current and future satisfaction of job. Thus performance of the whole organization will be enhanced. Decision making is very crucial in the organization, because it gives new skill needed to perform their job effectively and develop a quality work force. This study about decision making practice on workers performance also discuses about benefit, approaches and methods of decision. The study were conducted by gathering information though reviewing related documents in addition to the main primary sources questionnaire both, open and closed ended questions that were distributed to all employees in the organization . The researcher used census techniques (100% of the total population of 48 employees of the College. These employees subjected to the study were employees of Queens College Administration who were managerial and non-managerial staffs. From 48 employee among these questioner six were not returned and six did not provide inconsistence information and 36 employees answered questioner that distribute through the researcher. After the desired information was gathered, it was analyzed precisely using tables, percentages and generalization. Generally more than half of the employees did not take part in the process of decision making. As a result this becomes a ground for employees are dissatisfaction and awe ring employees about the objective of taking part in decision making the respective bodies and give invaluable time aware them.